Early administration of fibrinogen concentrates improves the short‐term outcomes of severe pelvic fracture patients. Issue 3 (2nd April 2017) - Inokuchi, Koichi; Sawano, Makoto; Yamamoto, Koji; Yamaguchi, Atsushi; Sugiyama, Satoru
Abstract : Aim: Hemorrhage from pelvic fracture is a major cause of mortality after blunt trauma. Several studies have suggested that early fibrinogen supplementation improves outcomes of traumatic hemorrhage. Thus, we revised our massive transfusion protocol (MTP) in April 2013 to include early off‐label administration of fibrinogen concentrate. The objective of this study was to evaluate the impact of the revision on the short‐term outcomes of pelvic fracture patients. Methods: This was a single‐center, retrospective, cohort study. A total of 224 consecutive pelvic fracture patients hospitalized in Saitama Medical Center (Saitama, Japan), 115 before the revision (Group E) and 109 after (Group L), were enrolled. Characteristics of the patients were compared between the groups. Impacts of the revision were evaluated by hazard ratios adjusted for characteristics, injury severity, and coagulation status using Cox's multivariate proportional hazard model. The impact was also evaluated by log–rank test and relative risk of 28‐day mortality between the groups. Results: The characteristics were equivalent between the groups. The multivariate analysis revealed that the revision of MTP was significantly related to improved survival with an adjusted hazard ratio (95% confidence interval) of 0.45 (0.07–0.97). The log–rank test gave χ 2 ‐test values of 5.2 ( P = 0.022) and 6.7 ( P = 0.009), and the relative risks were 0.37 (0.15–0.91) and 0.33 (0.13–0.84), in patients with all Injury Severity Scores and Injury Severity Score ≥21, respectively. Conclusion: The revision of MTP to include aggressive off‐label treatment with fibrinogen concentrate was related to improved short‐term outcomes of severe pelvic fracture patients. However, due to the limitations of the study, the improvement could not be attributed totally to the revision. Abstract : Twenty‐eight‐day survival curves of pelvic fracture patients compared between treatment groups. Broken lines represent the curve of Group E (those hospitalized before April 2013) and solid lines represent that of Group L (those hospitalized in April 2013 and later). The curves of patients with all Injury Severity Scores (top) and those of patients with Injury Severity Score ≥21 (bottom) are shown.